2018
DOI: 10.3389/fmicb.2018.00666
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Fungal Endophyte Assemblages in Root-Parasitic Plant Cynomorium songaricum and Its Host Nitraria tangutorum

Abstract: Endophytic fungi are an integral part and even seen as host organs of plant, influencing physiology, ecology, and development of host plants. However, little is known about micro-ecosystems and functional interactions of endophytic fungi in root-parasitic interactions of Cynomorium songaricum and its host Nitraria tangutorum. Here, distribution and dynamics of endophytic fungi were objectively investigated in their associations with C. songaricum and N. tangutorum based on mycobiome studies using high-throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…from the root of Dendrobium moniliforme was able to promote the growth and development of Rhynchostylis retusa. This supported the finding of Cui et al (2018) who reported earlier the ability of three endophytes isolates of F. redolens KY379544, F. nematophilum KY379572 and F. nematophilum KY379764 to promote the germination of C. songaricum seeds. Moreover, metabolites produced by several Fusarium spp.…”
Section: Improve Plant Resistance Against Abiotic Stressessupporting
confidence: 91%
“…from the root of Dendrobium moniliforme was able to promote the growth and development of Rhynchostylis retusa. This supported the finding of Cui et al (2018) who reported earlier the ability of three endophytes isolates of F. redolens KY379544, F. nematophilum KY379572 and F. nematophilum KY379764 to promote the germination of C. songaricum seeds. Moreover, metabolites produced by several Fusarium spp.…”
Section: Improve Plant Resistance Against Abiotic Stressessupporting
confidence: 91%
“…The samples from the final rinse solution were cultured using the potato dextrose agar (PDA) plate for 72 h at 28 °C. No fungal growth was observed on the PDA media, which suggested that root samples were effectively surface-sterilized (( Cui Vinod & Gang, 2018 )). All root samples were labeled and immediately placed on ice and stored at liquid nitrogen until total DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Besides bacterial communities, endophytic fungi also inhabit the inner tissues of parasitic plants. For instance, the rootparasitic plant Cynomorium songaricum parasitise Nitraria tangutorum, a flowering shrub from the Nitrariaceae family, harbours several fungal species assemblages belonging to the phylum, Ascomycota, Basidiomycota and Zygomycota [67]. Microbial communities play diverse roles during the growth and development and parasitism of parasitic plants on their host plants.…”
Section: Microbiomes Of Parasitic Plants and Their Hostsmentioning
confidence: 99%
“…Microbial communities play diverse roles during the growth and development and parasitism of parasitic plants on their host plants. For instance, some species of the genus, Fusarium, promote parasite seed germination, while symbiosis of arbuscular mycorrhizal fungi (Glomus mosseae) and rhizobia can alleviate plant host damage by root hemiparasites [67,68]. Nitrogen-fixing bacteria associated with host plants may indirectly benefit parasitic plants through efficient N 2 -fixation and their availability to the parasite during host attachment [69,70].…”
Section: Microbiomes Of Parasitic Plants and Their Hostsmentioning
confidence: 99%